High-Risk Analysis of Vertebral Compression Fractures With Type 2 Diabetes Mellitus: Site-Specific Volumetric Bone Mineral Density - Ying Liu; Lei Gao; Min Li; Wei Zhang; Yan Wang; Jian Zhao (International Journal of Endocrinology)
Conclusions: Vertebral compression fractures and the confusion between T2DM and vBMD may be all caused by the heterogeneous distribution of vBMDs. The higher risk of T2DM with vertebral compression fractures may be associated with the different loss rate of global and site-specific vBMD, independent of vBMD itself.